Cardiac Biomarkers and Risk of Atherosclerotic Cardiovascular Disease in Patients with CKD. Issue 5 (26th May 2022) - Lidgard, Benjamin; Zelnickv, Leila; Anderson, Amanda H.; Feldman, Harold; Go, Alan; He, Jiang; Kansal, Mayank; Mohanty, Madhumita Jena; Mehta, Rupal; Shlipak, Michael G.; Soliman, Elsayed; Weir, Matt R.; et al.
Key Points: Four different cardiac risk markers were strongly associated with interim atherosclerotic disease in a cohort of participants with CKD. These associations may highlight important mechanisms for the development of atherosclerosis in CKD. Visual Abstract: Abstract : Background: Several cardiac biomarkers of cardiac stress, inflammation, and fibrosis (N-terminal pro brain-type natriuretic peptide [NT-proBNP], high-sensitivity troponin T [hsTnT], growth differentiation factor 15 [GDF-15], and soluble ST2 [sST2]) have been associated with atherosclerotic disease in the general population. We hypothesized that these cardiac biomarkers may also be associated with the atherosclerotic cardiovascular disease in patients with CKD. Methods: We analyzed levels of NT-proBNP, hsTnT, GDF-15, and sST2 in a cohort of 2732 participants with mild to moderate CKD from the Chronic Renal Insufficiency Cohort (CRIC) study. Outcomes included incident atherosclerotic disease, defined as the first instance of myocardial infarction, stroke, or peripheral vascular disease. We used Cox proportional hazard models to the test the association of each cardiac biomarker with risk of incident atherosclerotic disease, adjusting for multiple possible confounders. Results: When modeled continuously (per SD increase in the log-transformed biomarker), NT-proBNP, hsTnT, GDF-15, and sST2 were significantly associated with incident atherosclerotic disease after adjustment for multiple potential confounders: (NT-proBNP HR, 1.51; 95% CI, 1.27 to 1.81; hsTnT HR, 1.61; 95% CI, 1.38 to 1.89; GDF-15 HR, 1.44; 95% CI, 1.19 to 1.73; and sST2 HR, 1.19; 95% CI, 1.04 to 1.36). Conclusions: NT-proBNP, hsTnT, GDF-15, and sST2 were significantly associated with incident atherosclerotic cardiovascular disease in patients with CKD. These associations may highlight important mechanisms for the development of atherosclerotic disease in CKD.